Nov pristop k preračunu aritmetičnega srednjega odstopanja profila pri kopirnem frezanju - Peterka, Jozef (Strojniški vestnik, 2004)
Surface roughness as a result of milling with a cylindrical ball-end cutter isdetermined in the technical literature, as it is in university textbooks, relatively infrequently. The problem is usually simplified, which means simplified relations for the calculations of theoretical surface roughness during copy milling with cylindrical ball-end cutters are introducedČ the calculation of parameter Rz, and the maximum height of the undulation profile.In this contribution an improved calculation, not only for parameter Rz , but also for parameter Ra, the arithmetical mean deviation of the profile, is presented. The paper presents new equations for the direct calculation of the arithmetical mean deviation of the transverse and longitudinal profiles during copy milling on a plane (face) surface and an oblique surface.
Keywords: frezanje kopirno; finiširanje; hrapavost površin; oblike proste; hrapavost; frezanje